2002
DOI: 10.1152/ajpregu.00664.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of 20-hydroxyeicosatetraenoic acid in the renal and vasoconstrictor actions of angiotensin II

Abstract: .-The present study examined the effects of ANG II on the renal synthesis of 20-hydroxyeicosatetraenoic acid (20-HETE) and its contribution to the renal vasoconstrictor and the acute and chronic pressor effects of ANG II in rats. ANG II (10 Ϫ11 to 10 Ϫ7 mol/l) reduced the diameter of renal interlobular arteries treated with inhibitors of nitric oxide synthase and cyclooxygenase, lipoxygenase, and epoxygenase by 81 Ϯ 8%. Subsequent blockade of the synthesis of 20-HETE with 17-octadecynoic acid (1 mol/l) increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
141
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(155 citation statements)
references
References 53 publications
14
141
0
Order By: Relevance
“…For example, ANG II and endothelin stimulate the renal formation of 20-HETE, which contributes to the renal vasoconstrictor and natriuretic actions of these hormones (11,12,35). The expression of CYP4A enzymes and the formation of 20-HETE are also elevated in the kidney of ANG II-infused hypertensive rats (1), and 20-HETE contributes to the development of hypertension and end-organ damage in this model (1,27,28). Vasopressin is another vasoconstrictor peptide that activates phospholipase A2 and releases AA (31).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, ANG II and endothelin stimulate the renal formation of 20-HETE, which contributes to the renal vasoconstrictor and natriuretic actions of these hormones (11,12,35). The expression of CYP4A enzymes and the formation of 20-HETE are also elevated in the kidney of ANG II-infused hypertensive rats (1), and 20-HETE contributes to the development of hypertension and end-organ damage in this model (1,27,28). Vasopressin is another vasoconstrictor peptide that activates phospholipase A2 and releases AA (31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that CYP metabolites of AA play an important role as second messengers in the regulation of the tubular and vascular effects of peptide hormones and growth factors (1,3,37,40). For example, ANG II and endothelin stimulate the renal formation of 20-HETE, which contributes to the renal vasoconstrictor and natriuretic actions of these hormones (11,12,35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations